SISTEM INFORMASI PENJUALAN KACAMATA PADA OPTIK CITRA BERBASIS WEBSITE - Wati, Nila; -, Riswan; -, Amel (LP2M Universitas Nurdin Hamzah, 2023)
Optics is a tool that works on the principle of light. Optical tools facilitate human life in seeing or perpetuating everything. This study aims to build a sipin optical image information system in order to increase sales for the store, by selling goods to consumers online which so far are still manual. This system is built using the PHP programming language and uses the Mysql database storage media. The inputs are admin data, product data, catalog data, order data, customer data and order confirmation. The input data will be processed in menu ordering and transactions. Meanwhile, the output produced is in the form of customer reports, product reports and order reports. The results show that with the construction of this application, the ordering process, transactions, and information are faster to customers so as to minimize errors and the process of reporting to the owner of the Sipin optical image can be achieved without any errors.